Structural performance of CFRP-strengthened concrete-filled stainless steel tubular short columns. (15th March 2019) - Sharif, Alfarabi M.; Al-Mekhlafi, Galal M.; Al-Osta, Mohammed A.
Highlights: Performance of CFRP-strengthened concrete-filled stainless steel tubular columns has been investigated experimentally. FE modeling captured the experimental response reasonably well. An analytical model to predict the load carrying capacity has been developed. Abstract: The use of concrete-filled stainless steel tubular (CFSST) members is relatively innovative and new. CFSST columns can be used for bridge piers, multi-story buildings and other supporting structures. However, a common mode of failure with these type of tubular composite columns is inelastic outward local buckling occurring at the column ends. Therefore, this paper presents the results of experimental, numerical and analytical investigations into the behavior of circular CFSST columns strengthened by carbon fiber reinforced polymer (CFRP) wrap and subjected to axial compression loading. The experimental investigation comprised three series of tests. The main variables tested were the diameter to thickness ratio of the stainless steel tube and the thickness of the CFRP wrap. 3D finite element models (FEMs) were developed for CFRP-wrapped CFSST columns using the ABAQUS software and were validated with experimental results. An extensive parametric study was carried out by using the validated FEMs. It was shown from the experimental and FEMs results that CFRP jacketing was highly effective in improving the axial load carrying capacity and axial shortening capacity of the CFSST columns. Finally, an analytical model based on the FE parametric study results was proposed to predict the axial load carrying capacity of the CFRP-wrapped CFSST columns.